Investigating the Impact of Fly-Ash Additive on Viscosity Reduction at Different Temperatures: A Comparative Analysis - Tuan-Anh Bui; Ngoc-Tam Bui (Applied Sciences, 2023)
The viscosity of lubricating oils is influenced by fly-ash additives and temperature, as they play a crucial role in regulating the viscosity of oils. Fly-ash additives are added to lubricating oils to improve oxidation resistance and prevent deposit formation, which may reduce viscosity loss at high temperatures. This study aimed to investigate the impact of fly-ash additives and temperature on the viscosity of oils B, C, and A. The experimental methodology involved comparing the viscosity of these oils with and without the addition of a 0.5% fly-ash additive. Viscosity measurements were taken at different temperatures. The results showed significant changes in viscosity after incorporating the fly-ash additive. At 25 °C, oils B, C, and A exhibited viscosity increases of 6.2%, 8.1%, and 13.8%, respectively, compared to the samples without the additive. Similarly, at 75 °C, the viscosity increments were 10.2%, 11.5%, and 22.8% for oils B, C, and A, respectively. At 85 °C, the corresponding increments were 11.1%, 16.6%, and 32.8%. These findings highlight the effectiveness of fly-ash additives in reducing the impact of temperature on oil viscosity, with oil A demonstrating the highest efficacy. By adjusting the viscosity of the oil at different temperatures, the fly-ash additives contribute to maintaining stable lubricating performance. Understanding the influence of fly-ash additives and temperature on oil viscosity is crucial for optimizing the performance of lubricants across various temperature conditions. Additionally, this knowledge assists in selecting the appropriate additive ratios for specific applications, thereby ensuring optimal lubricant performance.